Methylation-associated silencing of miR-193a-3p promotes ovarian cancer aggressiveness by targeting GRB7 and MAPK/ERK pathways - Chen, Kangmei; Liu, Michelle Xin; Mak, Celia Sze-Ling; Yung, Mingo Ming-Ho; Leung, Thomas Ho-Yin; Xu, Dakang; Ngu, Siew-Fei; Chan, Karen Kar-Loen; Yang, Huijuan; Ngan, Hextan Yuen-Sheung; Chan, David Wai (Theranostics, 2018)
Human growth factor receptor-bound protein-7 (GRB7) is a pivotal mediator involved in receptor tyrosine kinase signaling and governing diverse cellular processes. Aberrant upregulation of GRB7 is frequently associated with the progression of human cancers. However, the molecular mechanisms leading to the upregulation of GRB7 remain largely unknown. Here, we propose that the epigenetic modification of GRB7 at the post-transcriptional level may be a crucial factor leading to GRB7 upregulation in ovarian cancers. The upstream miRNA regulators were predicted by analysis. Expression of GRB7 was examined by qPCR, immunoblotting and immunohistochemical analyses, while levels were evaluated by qPCR and hybridization in ovarian cancer cell lines and clinical tissue arrays. MS-PCR and pyrosequencing analyses were used to assess the methylation status of . Stable overexpression or gene knockdown and Tet-on inducible approaches, in combination with and tumorigenic assays, were employed to investigate the functions of GRB7 and in ovarian cancer cells. Both and its isoform, , directly targeted the 3' UTR of GRB7. However, only showed a significantly inverse correlation with GRB7-upregulated ovarian cancers. Epigenetic studies revealed that methylation-mediated silencing of led to a stepwise decrease in expression from low to high-grade ovarian cancers. Intriguingly, not only modulated GRB7 but also ERBB4, SOS2 and KRAS in the MAPK/ERK signaling pathway to enhance the oncogenic properties of ovarian cancer cells and . : These findings suggest that epigenetic silencing of by DNA hypermethylation is a dynamic process in ovarian cancer progression, and may be explored as a promising miRNA replacement therapy in this disease.